Field electron emission enhanced streamer cold plasma interaction on seed surface wettability - Srisonphan, Siwapon; Kasemsuwan, Varakorn (My University, 2021)
Hybrid streamer cold plasma (HSCP) can be used in nanoscale surface modification, especially for curved biological surfaces. Here, the HSCP was applied to a rice (Oryza sativa L.) seed under different gas ambient and electric field distributions. Seed wettability enhancement (water imbibition (WI) and apparent contact angle (ACA)) is the primary method used to understand the dynamic of plasma interaction on biological surfaces. The extremely non-uniform electric field is directly responsible for plasma generation, via fringe field enhanced electron emission, which consequently impacts the ionization process. Further, this process is indirectly related to the plasma-enhanced electrochemical and physical reactions on biological nanoscale surface etching and functionalization. Despite being generated by means of different plasma mechanisms, the water imbibition time (WItime) on the top and bottom (shadow) of treated seed surfaces show similar characteristics, namely exponentially fast decay right after treatment, and a consequent linear decrease until reaching the saturation level. The stronger the corona discharge plasma, the less the difference in surface functionalization between the top and bottom surfaces. We demonstrate the model of WItime enhancement as a function of treatment time based on fringe field enhanced electron emission mediated impact ionization and reactive species (RS) generation for surface transformation.
Keywords: Electric field; Field electron emission; Hydrophilicity; Hydrophobicity, Nanoscale surface functionalization; Impact ionization; Streamer cold plasma